The Effect of Organizational Justice Perception on Ethical Sensitivity in the Health Sector - Sümeyye Hekim; Harun Kırılmaz (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
Organizational justice is considered the cause of many individual and corporate results. It is also thought to have significant effects on employees. Justice, which is one of the fundamental values of the organization, affects the attitudes and behaviors of the employees. Therefore, while it is necessary for social organizations, it is even more crucial for health institutions. The culture of injustice perceived by nurses not only harms the health institution but also leads to more critical problems. In addition to the necessity of justice, essential health services include uncertain and high-risk situations to protect and support human health has increased the need for ethical sensitivity. In this context, the study aims to reveal the effect of nurses' perceptions of organizational justice on ethical sensitivity levels. The “Organizational Justice Perception Scale” developed by Niehoff & Moorman (1993) and the “Ethical Sensitivity Questionnaire” developed by Lutzen (1994) were used in the research conducted in one public and two private hospitals in Sakarya. Descriptive statistical methods, independent samples t-test, one-way analysis of variance (ANOVA), correlation analysis and regression analysis were used to analyze the data. According to the study's findings, a low-level positive correlation was found between general organizational justice perceptions and ethical sensitivity levels. Among the sub-dimensions of the scales, it was determined that the highest relationship was between the dimensions of fair distribution and orientation. As a result, it is expected that there will be an increase in ethical sensitivity levels depending on the rise in nurses' perceptions of organizational justice.